Deep-scattering layer, gas-bladder density, and size estimates using a two-frequency acoustic and optical probe - Kloser, Rudy; Ryan, T.; Keith, G.; Gershwin, L. (2016)
© 2016 International Council for the Exploration of the Sea. All rights reserved.Estimating the biomass of gas-bladdered organisms in the mesopelagic ocean is a simple first step to understanding ecosystem structure. An existing two-frequency (38 and 120 kHz) acoustic and optical probe was lowered to 950 m to estimate the number and size of gas-bladders. In situ target strengths from 38 and 120 kHz and their difference were compared with those of a gas-bladder resonance-scattering model. Predicted mean equivalent spherical radius gas-bladder size varied with depth, ranging from 2.1 mm (shallow) to 0.6 mm (deep). Density of night-time organisms varied throughout the water column and were highest (0.019 m-3) in the 200-300 m depth range. Predictions of 38 kHz volume-backscattering strength (Sv) from the density of gas-bladdered organisms could explain 88% of the vessel's 38 kHz Sv at this location (S 40.9, E 166.7). Catch retained by trawls highlighted the presence of gas-bladdered fish of a similar size range but different densities while optical measurements highlighted the depth distribution and biomass of gas-inclusion siphonophores. Organism behaviour and gear selectivity limits the validation of acoustic estimates. Simultaneous optical verification of multifrequency or broadband acoustic targets at depth are required to verify the species, their size and biomass.